Implementation of Story Method in Introducing Prosocial Behavior Students in Elementary School - Maulana, Agis; Muharam, Agus; Hikamudin, Moch. Irfan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Behavior is basically goal oriented with other meanings, our behavior is generally motivated by a desire to achieve certain goals. As for specific objectives, are not always known consciously by individuals. The basic thing about behavior is an activity, in fact we can state that behavior is a series of activities. Prosocial behavior is behavior that has the intention to change the physical state of the recipient of assistance from less good to better. Actions that benefit others such as sharing with others who bring benefits to those people over themselves, comfort or help others to achieve their goals or make others happy by praising their behavior are called prosocial behavior. Storytelling is one alternative to introduce prosocial behavior in elementary school students. Therefore, this storytelling method will be effective to be used to introduce prosocial behavior in children. This study aims to find a way to introduce prosocial behavior through the method of telling stories by the teacher to children and to find out the results of the application of the method of telling stories in introducing prosocial behavior